PENGUKURAN TINGGI DAN TUTUPAN KANOPI POHON DI TAMAN SAINS, KECAMATAN DUREN SAWIT, KOTA JAKARTA TIMUR - Chaerunnisa, Tiara Putri; Shabrina, Syifa Mutiara; Sulistiyanto, Tabitha Qotrunnada; Suri, Mutiara Hasna Putri; Suryanda, Ade (Universitas Pakuan, 2023)
To find out or predict the potential of a particular stand or community is to take measurements. Measurement is used as the main determining factor that influences the accuracy of the data obtained. Measuring tree height is an important variable in providing a quantitative description of trees and stands that can determine the quality of stand locations and estimate several parameters. Likewise with tree canopies, the canopy or crown of a tree is a condition where the branches and leaves of a tree form overlapping each other. The aim of this research is to determine the height and canopy cover of several tree samples taken from the research location, namely Science Park, Duren Sawit District, East Jakarta City. The method used to collect tree height data is by using an inclinometer, and to measure tree canopy cover, it is measured using the GLAMA application. The results of this research showed that the Pinus merkusii tree was the tree with the highest height, namely 25.7 meters and the Leucaena leucocephala tree was the shortest tree, namely 2.4 meters. The tree height results were obtained based on tree height measurements carried out using trigonometry principles. Meanwhile, the largest Canopy Cover Index percentage was found in the Leucaena leucocephala tree, namely 77.48% and the smallest Canopy Cover Index was found in the Mangifera indica tree, which was 56.22%, with the largest and smallest percentages having a difference of 21.26%.. This difference was obtained through processing data obtained through the GLAMA application.